2005
DOI: 10.1016/j.febslet.2005.01.057
|View full text |Cite
|
Sign up to set email alerts
|

WRKY group IId transcription factors interact with calmodulin

Abstract: Calmodulin (CaM) is a ubiquitous Ca 2+ -binding protein known to regulate diverse cellular functions by modulating the activity of various target proteins. We isolated a cDNA encoding AtWRKY7, a novel CaM-binding transcription factor, from an Arabidopsis expression library with horseradish peroxidase-conjugated CaM. CaM binds specifically to the Ca 2+ -dependent CaM-binding domain (CaMBD) of AtWRKY7, as shown by site-directed mutagenesis, a gel mobility shift assay, a split-ubiquitin assay, and a competition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(133 citation statements)
references
References 26 publications
3
130
0
Order By: Relevance
“…An earlier study has shown that WRKY39 is a calmodulin-binding protein ( Fig. 1A; Park et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study has shown that WRKY39 is a calmodulin-binding protein ( Fig. 1A; Park et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The role of WRKY39 as a positive regulator in thermotolerance is also consistent with possible regulation of WRKY39 by calcium, a second messenger in A. thaliana. Calmodulin (CaM) interacts with the WRKY39 protein (Park et al, 2005) and calcium is involved in HS in plants through CaM (Liu et al, 2008;Zhang et al, 2009). Calcium does not appear to be involved in the classic HS signaling pathways, i.e.…”
Section: Galley Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that wRKY TFs interact with calmodulin, which binds to the C-motif (DxxvxKFKxvISLLxxxR) that is present in some group IId wRKY proteins (Park et al 2005). This implicates group IId wRKY TFs in transducing Ca 2+ signals.…”
Section: Interactomicsmentioning
confidence: 96%
“…CaM can bind to a highly conserved Ca 2+ -dependent CaMbinding domain (CaMBD) in the WRKY TFs belonging to the Group IId (Park et al 2005). Although OsWRKY47 does not contain typical CaM binding domains, its interaction with a CaMBP would suggest a possible role in the propagation of signals triggered by changes in cellular Ca 2+ homeostasis.…”
Section: (D) (A) (B) (C) (E)mentioning
confidence: 99%